Iron-Catalyzed Formation of C–Se and C–Te Bonds through Cross Coupling of Aryl Halides with Se(0) and Te(0)/Nano-Fe3O4@GO - Kassaee, Mohammad Zaman; Motamedi, Elaheh; Movassagh, Barahman; Poursadeghi, Samira (Synthesis, 2013)
The formation of C–Se and C–Te bonds is of synthetic and biological importance. Graphene oxide based nano-Fe3O4 (nano-Fe3O4@GO) is used as a reusable catalyst for the efficient synthesis of diselenides and ditellurides, through cross coupling of Se(0) or Te(0) with aryl iodides. The magnetic heterogeneous catalyst could be easily recovered and reused many times without significant loss of catalytic activity. In addition the superiority of nano-Fe3O4@GO over pristine nano-Fe3O4 is established.
Keywords: graphene oxide; cross coupling; recyclability; nano-Fe3O4 catalyst; diselenide; ditelluride